The strengths of Aboriginal and Torres Strait Islander children, parents and carers in Footprints in Time - Sartbayeva, A; Skelton, F; Atkinson, J (My University, 2015)
Since 2008 Aboriginal and Torres Strait Islander interviewers have been returning to Footprints in Time families across Australia to talk with parents, carers and children about their health, wellbeing, parenting, stressors, culture, and how to bring up strong children.  With six waves of data publically released, this presentation will focus on the factors that contribute to the social and emotional wellbeing of children in the study, those that hinder wellbeing, and the factors that are positively and negatively related to parents and carers confidence in their parenting.
Keywords: Culture -- Indigenous; Children -- Outcomes; Health -- Wellbeing; Health and wellbeing; Health; Culture; Children; Indigenous; Wellbeing; Outcomes; Health and wellbeing